Predictors of treatment efficacy and liver stiffness changes following therapy with Sofosbuvir plus Ribavirin in patients infected with HCV genotype 2. Issue 5 (30th January 2018) - Ohya, Kazuki; Akuta, Norio; Suzuki, Fumitaka; Fujiyama, Shunichiro; Kawamura, Yusuke; Kominami, Yoko; Sezaki, Hitomi; Hosaka, Tetsuya; Kobayashi, Masahiro; Kobayashi, Mariko; Suzuki, Yoshiyuki; Saitoh, Satoshi; et al.
Abstract : While the combination therapy of ribavirin (RBV) and sofosbuvir (SOF) is effective in genotype 2 HCV infection, the predictors of treatment efficacy and posttreatment changes in α‐fetoprotein (AFP) and liver stiffness (markers of hepatocellular carcinoma), remain unclear. In this study, 302 patients with chronic HCV genotype 2 infection were treated with SOF (400 mg) plus RBV (400‐1000 mg; based on body weight) for 12 weeks. We evaluated the efficacy and safety of treatment, as well as measured serum AFP, liver stiffness, and controlled attenuation parameter (CAP, a surrogate marker of steatosis) at baseline and within 48 weeks of treatment completion. The intention‐to‐treat analysis showed a sustained virological response (SVR) rate of 95.7%. None of the patients discontinued treatment due to side effects. Multivariate analysis identified pretreatment (no treatment with interferon), level of AFP (AFP; <10 μg/L), and RBV/body weight (BW) ratio (≥9.0 mg/kg) as independent predictors of SVR. The SVR rate in patients with two predictors of poor response (AFP ≥10 μg/L and RBV/BW ratio <9.0 mg/kg) was significantly lower than in other patients. In the SVR group, posttreatment AFP level and liver stiffness were significantly lower than at baseline. CAP tended to be higher after treatment than at baseline in all patients. SOF plus RBV combination therapy achieved a high SVR rate and was safe in HCV genotype 2 infected patients. Treatment reduced AFP levels and improved liver stiffness, but increased CAP.